2002
DOI: 10.1002/1521-3749(200201)628:1<81::aid-zaac81>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Neodymselenoxide auf dem Schnitt Nd2O3-SeO2

Abstract: Professor Paul Hagenmuller zum 80. Geburtstag gewidmet Inhaltsu È bersicht. Die phasenreinen Verbindungen auf dem quasibina È ren Schnitt Nd 2 O 3 ±SeO 2 : Nd 2 Se x O 3+2x im thermodynamischen Gleichgewicht wurden durch Festko È rperreaktion dargestellt und durch Ro È ntgendiffraktometrie, IR-Spektroskopie und DSC-Messungen charakterisiert. Dabei wurde neben den bereits bekannten Phasen Nd 2 Se 4 O 11 , Nd 2 Se 3,5 O 10 , Nd 2 Se 3 O 9 und Nd 2 SeO 5 die Existenz einer wei-teren Phase Nd 2 Se 1,5 O 6 nachgewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…Furthermore, because SeO 2 is a solid, typical solid-state synthesis techniques can be applied leading additionally to a large number of rare-earth selenites (Table ). Thermoanalytical investigations showed that in the systems M 2 O 3 /SeO 2 compounds with the compositions M 2 Se 4 O 11 , M 4 Se 7 O 20 , M 2 Se 3 O 9 , M 2 Se 2 O 7 , and M 2 SeO 5 exist. , …”
Section: Selenitesmentioning
confidence: 99%
“…Furthermore, because SeO 2 is a solid, typical solid-state synthesis techniques can be applied leading additionally to a large number of rare-earth selenites (Table ). Thermoanalytical investigations showed that in the systems M 2 O 3 /SeO 2 compounds with the compositions M 2 Se 4 O 11 , M 4 Se 7 O 20 , M 2 Se 3 O 9 , M 2 Se 2 O 7 , and M 2 SeO 5 exist. , …”
Section: Selenitesmentioning
confidence: 99%
“…This formula type RE 2 O 2 [SeO 3 ] (≡ RE 2 SeO 5 ) was long postulated from Oppermann et al [19][20][21][22][23] in various RE 2 O 3 /SeO 2 systems. Nevertheless, no single crystals were available to confirm this crystal structure, so it was only assumed via powder diffraction methods [19][20][21][22][23] [24] contains only two of these anions, while with the title compound the first rare-earth metal(III) oxoselenate(IV) was accessible with exclusively these sort of anions. The aim of the synthesis was a TlSc[SeO 3 ] 2 , however, which should be structurally similar to the alkali-metal scandium oxoselenates(IV) ASc[SeO 3 ] 2 (A = Na-Cs) [25]…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, in the literature is a rare-earth metal(III) oxoselenate(IV) known with two 'free' oxygen atoms per formula unit and the composition Sc 2 O 2 [SeO 3 ] [17,18]. This formula type RE 2 O 2 [SeO 3 ] (≡ RE 2 SeO 5 ) was long postulated from Oppermann et al [19][20][21][22][23] in various RE 2 O 3 /SeO 2 systems. Nevertheless, no single crystals were available to confirm this crystal structure, so it was only assumed via powder diffraction methods [19][20][21][22][23] [24] contains only two of these anions, while with the title compound the first rare-earth metal(III) oxoselenate(IV) was accessible with exclusively these sort of anions.…”
Section: Introductionmentioning
confidence: 99%
“…Die 80 M ol% -Se02-Phase (Sm2Se4On ) weist ein eigenständiges IR-Spektren, ähnlich dem des Nd2Se4Ou [5] auf.…”
Section: Die Ir-spektren Wurden An Einem Spekord M 80 Der Firma Carl unclassified
“…Nachdem wir das thermische Verhalten aller Pha sen des Schnittes Nd20 3-S e 0 2, ihre Charakterisie rung und erste thermodynamische Daten vorgestellt haben [5], soll hier die Beschreibung aller auf dem Schnitt Sm20 3-S e 0 2 existierender Phasen erfolgen. Außer für die drei von Castro et al [1 -3] gefun denen Phasen führen wir den Nachweis der Exi stenz zweier weiterer Phasen, einer 60 M ol% -Se02-Phase Sm2Sej 50 6 und einer 80 M ol% -Se02-Phase Sm2Se4On .…”
Section: Introductionunclassified